1994
DOI: 10.1530/jrf.0.1010077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes mellitus during the luteal phase of the oestrous cycle on preovulatory follicular function, ovulation and gonadotrophins in gilts

Abstract: Development of preovulatory follicles was studied during the oestrous cycle in two experiments designed to examine the effects of short-term lack of insulin on preovulatory follicular function and (Expt 2 only) ovulation. In Expt 1, on day 12 of the third postpubertal oestrous cycle, insulin treatment was discontinued in streptozocin-induced diabetic gilts (n = 4), and on day 18, ovaries were removed from the diabetic gilts and from four normal untreated gilts. Diabetic gilts had a higher percentage of macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 5 publications
2
12
0
1
Order By: Relevance
“…In the same manner, alloxan suppressed luteinizing hormone secretion in female rats (Kinoshita et al, 2004). Additionally, diabetic gilts did not exhibit estrous or ovulation (Cox et al, 1994). Luteinizing hormone surge was also absent in immature alloxan-induced diabetic rats that led to anovulation (Kirchick et al, 1978).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In the same manner, alloxan suppressed luteinizing hormone secretion in female rats (Kinoshita et al, 2004). Additionally, diabetic gilts did not exhibit estrous or ovulation (Cox et al, 1994). Luteinizing hormone surge was also absent in immature alloxan-induced diabetic rats that led to anovulation (Kirchick et al, 1978).…”
Section: Discussionmentioning
confidence: 77%
“…Specifically, diabetes mellitus suppresses luteinizing hormone secretion in streptozocin-induced diabetic rats (Cagampang et al, 1997) and disrupts estrous cycle (Cox et al, 1994). Estrous cycle is the period of reproductive cyclicity in animals that usually lasts for 4-5 days in rodents (Pineda, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes has been shown to reduce the number of ova ovulated or cause delays in embryonic development [5][6][7][8][9][10][11][12][13]. In an earlier study, we utilized a mouse model of streptozotocin-induced type I diabetes to show that diabetes also adversely affects the process of oocyte maturation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of the IGF-I system via alterations in IGFBPs could also be a method by which insulin influences follicular function. For example, Edwards et al (1996) reported an increase in IGFBP-1 and IGFBP-2 concentrations in diabetic gilts, and this could alter the IGF-I system by affecting (Cox et al, 1987a, b (Cox et al, 1994 (Edwards et al, 1996) (Qiu, 1995) …”
Section: Introductionmentioning
confidence: 99%